2020
DOI: 10.1007/s11162-020-09599-4
|View full text |Cite
|
Sign up to set email alerts
|

Well-Placed: The Geography of Opportunity and High School Effects on College Attendance

Abstract: Recent work has broadened the scope of school effectiveness research to consider not only academic achievement but also other outcomes, especially college attendance. This literature has argued that high schools are an important determinant of college attendance, with some contending that high schools matter more for college attendance than for academic achievement. A separate branch of research has illustrated how place-based opportunities facilitate college attendance. We merge these two literatures by askin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
3
11
0
Order By: Relevance
“…Commuting zones with higher than average percentages of residents with a bachelor's degree or higher were less likely to be classified as a college access desert, aligning with prior research that most students enroll in colleges near their high schools or community (Hillman & Weichman, 2016;Hirschl & Smith, 2020;Turley, 2009) and colleges employ large numbers of people with degreesa key component of the 'college town' archetype (Gumprecht, 2008). Of note is that commuting zones with higher than average unemployment rates had lower odds of being classified as a college access desert than commuting zone with average unemployment rates (0.63 times odds using sector classifications and 0.68 times odds using Carnegie Classifications).…”
Section: College Access Deserts In 2019supporting
confidence: 70%
“…Commuting zones with higher than average percentages of residents with a bachelor's degree or higher were less likely to be classified as a college access desert, aligning with prior research that most students enroll in colleges near their high schools or community (Hillman & Weichman, 2016;Hirschl & Smith, 2020;Turley, 2009) and colleges employ large numbers of people with degreesa key component of the 'college town' archetype (Gumprecht, 2008). Of note is that commuting zones with higher than average unemployment rates had lower odds of being classified as a college access desert than commuting zone with average unemployment rates (0.63 times odds using sector classifications and 0.68 times odds using Carnegie Classifications).…”
Section: College Access Deserts In 2019supporting
confidence: 70%
“…[44][45][46] These channels also allow students to get information about scholarships, loan repayment programs, or other training fellowships that may lower the cost of attending medical school. 44,47 Second, college and high school students who study science or related subjects and live close to a medical school may learn from local physicians who can be role models for their careers. 48,49 Another interesting finding concerns the growing gap in medical school applicants and matriculants from low-income and high-income counties from 2001 to 2015.…”
Section: Discussionmentioning
confidence: 99%
“…In the macrosystem, the students' culture, geographic location and socio-economic status often play a significant role in determining their level of engagement and subsequently the degree of success. These factors are proffered as possible marks of influence; several studies have demonstrated that elements such as geographic location and socioeconomic status, may have some impact on educational success (Cooper et al, 2017;Hirschl and Smith, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%